Welcome to Westonci.ca, where finding answers to your questions is made simple by our community of experts. Join our platform to get reliable answers to your questions from a knowledgeable community of experts. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.


Factor each expression completely.


Factor Each Expression Completely class=

Sagot :

[tex]Use:\\a^2-b^2=(a-b)(a+b)\\(a\pm b)^2=(a^2\pm2ab+b^2\\==============================\\27.\\18z^2-8=2(9z^2-4)=2\left[(3z)^2-2^2\right]=2(3z-2)(3z+2)\\\\29.\\2a^2-16a+32=2(a^2-8a+16)=2(a^2-2a\cdot4+4^2)=2(a-4)^2\\=2(a-4)(a-4)\\\\31.\\12x^2+36x+27=3(4x^2+12x+9)=3[(2x)^2+2\cdot2x\cdot3+3^2]\\=3(2x+3)^2=3(2x+3)(2x+3)[/tex]

[tex]33.\\3x^2-24x-27=3(x^2-8x-9)=3(x^2+x-9x-9)\\=3[x(x+1)-9(x+1)]=3(x+1)(x-9)\\\\35.\\-x^2+5x-4=-(x^2-5x+4)=-(x^2-x-4x+4)\\=-[x(x-1)-4(x-1)]=-(x-1)(x-4)\\\\37.\\x^2-y^2=(x-y)(x+y)\\\\39.\\-6z^2-600=-6(z^2+100)[/tex]
Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Thank you for visiting Westonci.ca, your go-to source for reliable answers. Come back soon for more expert insights.